The Role of Women as Community Development Cadres in Stunting Prevention through Animal Protein-Based Product Processing Technology in Kampung Sewu Village, Surakarta - Swastike, Winny (Journal of Innovation and Applied Technology, 2024)
This activity aims to examine the role of women cadres in community development in stunting prevention through processing technology for vegetable and animal protein-based products, especially in Kampung Sewu Village, Surakarta City. Stunting is a significant chronic nutritional problem in Indonesia, especially in children under five. One form of prevention is through nutritional interventions of protein sources based on processed plant and animal products. Through the empowerment of female cadres, who are often local community leaders,